SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN SLUKE KABUPATEN REMBANG - Juanda, 12.52.02.0190; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to assess and analyze : 1) Supervision of the principal mediating effecct of competence and motivation, 2) Supervision principal have mediating influence on the performance of competence and motivation of teachers. The locationof research is in elementary school measurement school in the Sluke district Rembang regency with the sample totaled 124 respondents using census method of measurement using a likert scale with live is alternative answer: Veryagree; Agree; Fast agree; Not agree and Very not agree Theresult of the regression analysis for the first model generales coefficient of determination of 0,035, which means that the ability of the independent variables in explaining the variation in the variable idependent (variable supervision of the principal amount of 3,5%, of the remaining 96,5%, is explained by other variables autis ide the model while the second, model obtained coefficient of determination of 0,150 means that the ability of the independent variables in explaining the variation in the dependent variable(variable performance of teachers) by 15%. of the remainder by 85% is explained by other variables outside the model. This study shows that the 1)Pedagogicalcompetence does not affect the performance of teachers. 2) Motivation affect on teacherperformance. 3) Supervision of theÂ principalÂ does not positive effect on theperformance of teachers, 4) Supervision of principal does not moderates the pedagogical competenceof teacher performance, 5) Supervision of the principal motivation moderates on teacher performance . Keywords : Pedagogical competence, Motivation, Supervision of school principals and teachers